تحديد الاحتياجات التدريبية وأثرها على تطوير الأداء دراسة ميدانية على الكليات التعليمية الخاصة بسلطنة عمان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن الاحتياجات التدريبية هي مجموعة التغيرات الواجب إحداثها في الفرد والمتعلقة بمعلوماته وخبراته وأدائه وسلوكه واتجاهاته لكي يتمكن من أداء واجبات وظيفته بكفاءة أعلى، وتمثل عملية تحديد الاحتياجات التدريبية الأساس في صناعة التدريب وتقوم عليها جميع دعائم العملية التدريبية وتنمية الموارد البشرية، وتعتبر الأداة الأساسية التي من خلالها يتم التطوير والتنمية للأفراد. ولقد تناول البحث مدى تأثير تحديد الاحتياجات التدريبية على أداء الموارد البشرية في مؤسسات التعليم العالي الخاصة بسلطنة عمان. وقد توصلت الدراسة إلى وجود علاقة ذو دلالة معنوية بين فاعلية نظام الحوافز والولاء الوظيفي بالإضافة إلى وجود علاقة بين نظام الحوافز ومعدلات الإنتاج. Training needs are a set of changes that must be done on a certain individual’s knowledge, practice, performance, that he can do  his duties with more aptness. Specifying the training needs is considered the foundation in the training industry, on which all the training process basis and Human resources development depends. It is considered the main tool by which advancement and development of individuals is done. This research has included the training needs and their influence in the private educational colleges in the Sultanate of Oman, and has concluded the existence of relation between the efficiency of wages system and loyalty, in addition to the existence of relation between the wages system and the production rate.